Three dimensional simulation of thermal pad using nanomaterial, nano-silver in semiconductor and electronic component application - Mazlan, Mohamed; Rahim, Atan, Prof. Madya Dr.; Mohd Mustafa Al Bakri, Abdullah; Muhammad Iqbal, Ahmad; Mohd Huzaifah, Yusoff; Fathinul Najib, Ahmad Saad (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/